Current Account Imbalances can Structural Reforms Help to Reduce Them? - Kerdrain, Clovis (OECD Publishing, 2011)
This article explores the impact of structural policies on saving, investment, and current accounts in OECD and non-OECD economies. Since the current account effects of structural reforms are often complex and ambiguous from a theoretical perspective, new OECD empirical analysis is carried out. Reduced-form equations are estimated for a panel of 30 OECD countries as well as for a panel/cross-section of 117 OECD and non- OECD countries that relate saving, investment and current accounts to policy indicators and a set of macroeconomic control variables. This work suggests that structural reforms may influence saving, investment and current accounts through their impact on macroeconomic conditions such as productivity growth or public revenues and expenditures, but also more directly: i) higher social spending (in particular on health care) is found to lower the saving rate and thereby to weaken the current account, most likely reflecting lower precautionary saving; ii) product market liberalisation temporarily boosts investment and thus also weakens the current account; iii) financial market deregulation may lower the saving rate, though only in less developed countries; iv) stricter employment protection may be associated with lower saving rates if unemployment benefits are low, as well as with higher investment rates possibly due to greater substitution of capital for labour. A scenario analysis indicates that fiscal consolidation and structural reforms in the main world economies could significantly reduce current global imbalances, possibly by about one-third